Cognitive Biases and Socio-Occupational Functioning Mediate the Relationship between Executive Functions and the Severity of Psychopathology among Young Adults with Psychotic-like Experiences: 1-Year Follow-Up Study - Aleksandra Arciszewska-Leszczuk; Andrzej Cechnicki; Dorota Frydecka; Dawid Kruk; Łukasz Gawęda (Brain Sciences, 2024)
The aim of this study was to investigate whether Trail Making Test (TMT) performance is associated with the severity of psychopathological symptoms related to psychosis among young adults with elevated level of psychotic-like experiences (PLEs), and whether this relationship is mediated by cognitive biases and socio-occupational functioning. A total of 187 subjects from a larger population of 6722 young adults participated in this 1-year follow-up study. The inclusion criteria were an elevated level of PLEs (the highest score of the Prodromal Questionnaire) and a lack of schizophrenia diagnosis. Eventually, 134 subjects (71.6%) completed the TMT, as well as the DACOBS scale (cognitive biases), at baseline and were examined twice using the CAARMS (psychopathology) and SOFAS (socio-occupational functioning) scales. In the first (I) and second (II) measurements, the calculated effects indicate indirect-only mediations, which explained 35 and 38% of the variance of the CAARMS. The TMT B execution time was positively associated with the DACOBS scale (β = 0.19, p = 0.028), which was negatively related to the SOFAS I (β = −0.37, p < 0.001) and SOFAS II (β = −0.20, p = 0.016) measurements. A lower score on the SOFAS I predicted a higher score on the CAARMS I (β = −0.50, p < 0.001), and a lower SOFAS II predicted a higher score on the CAARMS II (β = −0.61, p < 0.001). Subtle EF dysfunctions may, over time, translate into a greater severity of symptoms related to psychosis in people with elevated PLEs, and this is mediated by a deterioration of their metacognition and socio-occupational functioning.